ANALISIS KEBIJAKAN ALIH FUNGSI LAHAN PERTANIAN TERHADAP KETAHANAN PANGAN DI JAWA BARAT - Muhamad Nur Afandi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
Agriculture is one of the sectors that have been relied on by the government of Indonesia since this sector is able to provide a recovery in dealing with the crisis occurred in Indonesia. It shows that agriculture is one of the mainstay sectors having a big potency to role as a trigger of the national economy recovery through the national food sustenance. The result of the analysis shows that in 1995-2006, there was 225,292-hectare or 1.82-percent rice field area turned into non-rice field area. It means that there is an 18,774-hectare field alteration occurred every year in West Java. The rice production in 1995-2006 was 1,304,853 ton meaning that there was 1.09 percent of discharge. Therefore, there is 108,738 ton reduction of rice production every year. On the whole, in the period of 1995-2006, the average rate of rice production was 9,936 ton and the agricultural productivity was 5.03 ton per year, although it was affected by the 18,774-hectare agricultural land alteration. If the preventive actions are not conducted immediately, the rice production cannot be maintained. On theother hand, the population keeps increasing. Thus, it can be predicted that West Java is going to encounter food crisis in 2021, particularly, the need of rice.The problems resulted from the conversion of rice field area should be analyzed. It should not only be based on its impact on the rice production but also on a wider perspective. It includes its effect on the political stability caused by the food scarcity, the inflicting social change, the decrease of life environment, mainly is related to the contribution of rice field function to water and soil conservation that guarantee the life of society in the future. To reduce the land functional shift, the government of West Java province needs to implement certain policies and strategies of controlling the conversion of rice field area since it is indeed very complicated. The strategies of controlling agricultural land functional shift need a holistic approach (contains the juridical instrument, the incentive instrument for the field’s owner, the instrument of district layout planning, and the location licensing). Moreover, to maintain the food sustenance in West Java, particularly to increase the rice production, apart from controlling the functional shift of field; an agricultural intensification should be applied through the application of an efficient agricultural technology that is location-specified and environment-oriented in order to be able to raise the cultureof science and agricultural technology in West Java.